ANSWER:
The product of two consecutive positive integers is 1332. The larger number is 37.
SOLUTION:
Given, the product of two consecutive positive integers is 1332.
Let the larger number be x.
Then the smaller number is x – 1 [as the given numbers are consecutive]
Product of the two numbers is 1332 → larger number
smaller number = 1332
x(x – 1) = 1332
(x)x – (x)(1) = 1332
![\begin{array}{l}{x^(2)-x=1332} \\ {x^(2)-x-1332=0}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g7ngk53zqtn16bj2qgaxfyruu9ck06ko99.png)
This is quadratic equation. let us find the x value by factorization method.
we need to make the two terms product as such that, difference of both numbers should be equal to 1, as x coefficient is 1.
![x^(2)-x-2 * 666=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ips8nq5i63yeronupsz52kwy24jpvs7gpz.png)
keep doing this until we get the difference equals to 1.
![x^(2)-x-4 * 333=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sspsv2or5ao0an9zzq37ztia6gdsfsv866.png)
![\mathrm{x}^(2)-\mathrm{x}-12 * 111=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hxv05881iangfqaickowa9nob1evzbjyar.png)
![x^(2)-x-36 * 37=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/s474bkve3e50umcgdjmm7ka2vx5cn09l8n.png)
we got difference 1 that is 37 – 36 = 1
writing the x coefficient in terms of those numbers (36, 37)
![\mathrm{x}^(2)-(37-36) \mathrm{x}-36 * 37=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7j5sxlab8sojha05ili4gqyun9djjkh700.png)
![x^(2)-37 x+36 x-36 * 37=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xf84anxkv75ce8lvy0b7472zjn0ht24gm4.png)
now, take the common terms
x(x – 37) + 36(x – 37) = 0
(x – 37)(x + 36) = 0
x – 37 = 0 or x + 36 = 0
x = 37 or -36
we can neglect -36, because given numbers are positive numbers.
Hence, the larger number is 37